2020
DOI: 10.1021/acs.jafc.0c04131
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Testing of Ester Pheromone Analogues for Two Fruitworm Moths (Carposinidae)

Abstract: A range of ester pheromone analogues for carposinid moths were synthesized and evaluated for biological activity. The analogues aimed to take advantage of the structural commonality of (7Z)-alken-11-ones found in this family. Analogues were tested on two pest species: Heterocrossa rubophaga and Coscinoptycha improbana. Two of the analogues, (2Z)-nonenyl nonanoate and (4Z)-heptyl undecenoate, elicited significant electroantennogram responses. Only (4Z)-heptyl undecenoate gave consistent responses with both moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…■ RESULTS AND DISCUSSION Synthesis. Starting with the previously prepared pheromone component (Z)-nonadec-12-en-9-one (1), 11 a series of functional group interconversions were attempted (Scheme 1). This began with the methylene analogue, (Z)-11-methylenenonadec-7-ene (2), which was prepared via Wittig olefination.…”
Section: ■ Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…■ RESULTS AND DISCUSSION Synthesis. Starting with the previously prepared pheromone component (Z)-nonadec-12-en-9-one (1), 11 a series of functional group interconversions were attempted (Scheme 1). This began with the methylene analogue, (Z)-11-methylenenonadec-7-ene (2), which was prepared via Wittig olefination.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Investigation in the literature showed that Camps et al had experienced similar problems with Lawesson reagent when trying to prepare moth pheromone-like structures and had to resort to more complicated methods, so attempts to form the thione were abandoned. 13 In a similar fashion to the functional group transformations listed above, the methyl ether analogue, (Z)-11-methoxynonadec-7-ene (6), was prepared from the alcohol precursor of the pheromone, 11 (Z)-nonadec-12-en-9-ol (5) (Scheme 2).…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations